PENGARUH AUDIT TENURE, DEBT DEFAULT, KUALITAS AUDIT DAN OPINI AUDIT TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novita Sari, Yustina Triyani (Jurnal Akuntansi, 2018)
An audit opinion of going concern is an audit opinion issued by the auditor to ascertain whether a certain company can still maintain its survival for a year coming. The variables used in this research are the audit tenure, debt default, audit quality and audit opinion. These objects of research are 23 companies operate in industry sector (manufactur) which is listed in Indonesia Stock Exchange (IDX) during period 2011-2016. For hypothesis testing result show that audit tenure does not have sufficient evidence of significant effect on the audit opinion of going concern, debt default does not have sufficient evidence of significant effect on the audit opinion of going concern audit opinion of going concern, quality audit does not have sufficient evidence of significant effect on the audit opinion of going concern the audit opinion of going concernand audit opinion there is liable to audit opinion from previous year of going concern.Â Keywords: Audit Opinion Of Going Concern, Audit Tenure, Debt Default, Quality Audit, And Audit Opinion From Previous Year